Building 'low-intensity' democracy in Haiti : the OAS contribution - Shamsie, Yasmine (2004)
Examines the Organization of American States' (OAS) efforts to restore and promote democracy in Haiti between 1990 and 2000. Reveals that marked contradictions emerged as the organisation tried to promote a democratic outcome while both supporting and facilitating the workings of a profoundly undemocratic economic and trading system. Concludes by reflecting on the fall of the country's president Jean-Bertrand Aristide. Examines the role of the OAS and other international actors in shaping events leading up to the collapse of his government.